Synthesis of Terminal Ethynyl Aryl Selenides and Sulfides Based on the Retro‐Favorskii Reaction of Hydroxypropargyl Precursors. Issue 55 (30th August 2017) - Lopes, Eric F.; Dalberto, Bianca T.; Perin, Gelson; Alves, Diego; Barcellos, Thiago; Lenardão, Eder J.
Abstract: The retro‐Favorskii reaction is an excellent way to achieve terminal alkynes. Methodologies that connect the synthesis of terminal alkynes and organochalcogen motifs are important for the construction of novel compounds. Fourteen new terminal alkynes containing either Csp −S or Csp −Se bonds were selectively prepared through the retro‐Favorskii reaction from the respective carbinol precursors. It was discovered that terminal chalcogen alkynes were stable for weeks if stored as a solution in hexanes. Abstract : By the book : Fourteen new terminal alkynes containing either Csp −S or Csp −Se bonds were selectively prepared through the retro‐Favorskii reaction from the respective carbinol precursors (see figure). The stability of terminal chalcogen alkynes in solution was also investigated.